2009
DOI: 10.2217/fon.09.82
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Sex Hormone Levels and Prostate Cancer: Effect of Prostate Cancer on Serum Testosterone Levels

Abstract: Androgens are essential for prostatic growth and development, but also play a significant role in the pathogenesis of prostate disease. The traditional view that higher testosterone levels represent a risk factor for prostate cancer (PCa) appears to have little evidentiary support. Some studies have described a relationship between lower testosterone levels and more advanced disease. Serum androgen levels, within a broad range, are thus suggested to show no association with PCa risk, whereas low rather than hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The final elongation step was performed at 72˚C for 10 min. Each PCR product (261 bp) was digested at 37˚C for 16 h by the restriction enzyme RsaI (5 units, Fermentas, Denmark) in order to determine the presence of the V89L variant (9), separated by the Microchip Electrophoresis system for DNA/RNA Fragment Analysis MCE ® -202 MultiNA (Shimadzu, Japan). The common SRD5A2-89V allele retained the RsaI restriction site at the polymorphic region and generated 21-, 62-and 169-bp frag-ments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final elongation step was performed at 72˚C for 10 min. Each PCR product (261 bp) was digested at 37˚C for 16 h by the restriction enzyme RsaI (5 units, Fermentas, Denmark) in order to determine the presence of the V89L variant (9), separated by the Microchip Electrophoresis system for DNA/RNA Fragment Analysis MCE ® -202 MultiNA (Shimadzu, Japan). The common SRD5A2-89V allele retained the RsaI restriction site at the polymorphic region and generated 21-, 62-and 169-bp frag-ments.…”
Section: Methodsmentioning
confidence: 99%
“…Androgens, testosterone and dihydrotestosterone (DHT) are actively involved in the growth and development of the prostate, and appear to be essential for carcinogenesis in the prostate gland (9). In total, 80-90% of prostate cancers are dependent on androgens at initial diagnosis, and endocrine therapy of prostate cancer is directed towards the reduction of serum androgens and inhibition of the androgen receptor (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Some early studies demonstrated that plasma T levels might be correlated with Gleason grade or time to progression after orchiectomy of CaP (3,4). However, other studies indicated no evidence of any association between plasma T, estradiol (E2), SHBG with Gleason score at the time of diagnosis (5, 6). Thus, there is insufficient evidence to support the hypothesis that higher blood levels of steroid hormones are associated with CaP development or progression.…”
Section: Introductionmentioning
confidence: 97%
“…There is conflicting evidence for the role of androgens in the development of prostate cancer (PC) [1]. In a previous study, it was reported that PC patients with a low dihydrotestosterone (DHT) level at diagnosis had a higher risk of dying from PC than those with a high level [2].…”
Section: Introductionmentioning
confidence: 99%